Signet ring cell cholangiocarcinoma in a patient previously operated for cholecystectomy: is there any connecting link? - Gupta, Priya; Karuna, Veer; Singh, Preeti; Verma, Nidhi (International Journal of Research in Medical Sciences, 2019)
Cholangiocarcinoma are malefic tumours of bile duct. Signet ring cell carcinoma (SRCC) is rare entity. Several risk factors have been attributed to its ethology, the main overriding link between two being chronic inflammation of the bile system. Cholecystectomy has also been a proposed risk factor. This study was undertaken in Department of Pathology at LLRM Medical College, Meerut. A 49 years old female, operated for cholecystectomy 1.5 year back in same hospital, now presented with chief complains of jaundice and abdominal discomfort. The blood chemistry revealed increased total bilirubin (13.7 mg/dl), Alkaline phosphatase (877.6 IU/L), Carbohydrate Antigen (CA) 199(184 U/ml) and Carcinoembryonic antigen (CEA) (14.5 ng/ml). Computed Tomography (CT) showed a stricture in mid Common bile duct (CBD). Excision of stricture was done using retrocholic hepatico-jejunostomy. Tissue was submitted for histopathology. Histopathological assessment showed SRCC. The patient failed to turn up for further management but returned back after a span of time presenting with gross ascites and pallor ultimately leading to death within 12 weeks of diagnosis. This was the first case of SRCC to arise in a patient who had a previous history of cholecystectomy. Whether there is some connecting link between the two is still not clear. Further studies are warranted in this direction to establish cholecystectomy as an etiological factor for cholangiocarcinoma.